2012
DOI: 10.1111/j.1440-1843.2012.02153.x
|View full text |Cite
|
Sign up to set email alerts
|

N‐terminal proB‐type natriuretic peptide levels aid the diagnosis of left ventricular dysfunction in patients with severe acute exacerbations of chronic obstructive pulmonary disease and renal dysfunction

Abstract: NT-proBNP remains an accurate biomarker for the diagnosis of left ventricular dysfunction associated with acute exacerbations of COPD. Threshold values of NT-proBNP were higher in patients with impaired renal function than in those with normal renal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 34 publications
(55 reference statements)
1
12
0
Order By: Relevance
“…These included ischaemic heart disease, [38, 40] pulmonary emboli, [41] arrhythmia, [32] aortic stenosis, [25] pulmonary hypertension, [42] renal impairment [32, 43]. However, these comorbidities were rarely reported or searched for systematically.…”
Section: Resultsmentioning
confidence: 99%
“…These included ischaemic heart disease, [38, 40] pulmonary emboli, [41] arrhythmia, [32] aortic stenosis, [25] pulmonary hypertension, [42] renal impairment [32, 43]. However, these comorbidities were rarely reported or searched for systematically.…”
Section: Resultsmentioning
confidence: 99%
“…In IPAH, NT-proBNP has been shown to correlate with RV function [39] and changes in serial NT-proBNP with treatment have been shown to predict survival [40]. In COPD, NT-proBNP has been shown to predict outcome following acute exacerbations of airways disease [41][42][43], identify those with concurrent left ventricular dysfunction [42,44] and function as a screening tool for PH in COPD [45]. Our study demonstrates that NT-proBNP reflects RV dysfunction in severe PH lung disease patients, predicts survival on univariate analysis and, in addition, change in NT-proBNP predicted survival.…”
Section: Discussionmentioning
confidence: 99%
“…NTproBNP has been used as a marker of heart failure, 2,8 and NTproBNP levels are elevated in patients with renal failure. 9 We found no significant differences in serum levels of aspartate aminotransferase, creatinine phosphokinase, blood urea nitrogen or creatinine between the E and FS groups. Therefore, we concluded that NTproBNP levels in the 2 different groups of patients were not affected by heart or renal status.…”
Section: Discussionmentioning
confidence: 83%